Effect of Chitosan Variation in Starch and Cellulose Based Biofoam - Ayu Lintang Cahyani; Vidrika Linda; Dody Guntama; Mubarokah N Dewi; Lukmanul Hakim (Universitas PGRI Semarang, 2023)
Styrofoam’s using as packaging is increasing. Styrofoam is difficult to decompose so alternatives such as biofoam are needed. This study explores the creation of eco-friendly packaging material by varying cellulose (0%, 3%, 5%, and 7%) and chitosan concentrations (0%, 2%, 4%, 6%, 8%, and 10%) in biofoam, aiming to replace non-biodegradable Styrofoam. Production is carried out by delignifying sugarcane bagasse and corn cobs with 10% NaOH, making tofu pulp starch and biofoam. The research focuses on tensile strength, absorption capacity, biodegradation, and morphology of the biofoam. Results indicate that chitosan concentration affects water absorption and biodegradation, while cellulose impacts tensile strength. The findings highlight the potential of biofoam made from tofu dregs, corn cobs, and sugar cane bagasse, offering a promising alternative to Styrofoam